2016
DOI: 10.1164/rccm.201512-2523oc
|View full text |Cite
|
Sign up to set email alerts
|

Development and Progression of Interstitial Lung Abnormalities in the Framingham Heart Study

Abstract: Rationale: The relationship between the development and/or progression of interstitial lung abnormalities (ILA) and clinical outcomes has not been previously investigated.Objectives: To determine the risk factors for, and the clinical consequences of, having ILA progression in participants from the Framingham Heart Study.Methods: ILA were assessed in 1,867 participants who had serial chest computed tomography (CT) scans approximately 6 years apart. Mixed effect regression (and Cox) models were used to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

17
218
5
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 261 publications
(256 citation statements)
references
References 26 publications
17
218
5
8
Order By: Relevance
“…In three previous studies the prevalence of ILAs ranged from 3% to 10%, with estimates of progression ranging from 20% at 2 years to 46% at 4 years [6,12,13]. In a recently published study by ARAKI et al [14], the results were comparable: ILAs were prevalent in 6% of total cases, and in 3% (n=53) of the initial scans, of which 43% (n=23) demonstrated progressive imaging abnormalities over ∼6 years of follow-up time. Consistent with previous reports, the progression of ILAs to imaging findings consistent with usual interstitial pneumonia (UIP) was seen in 4% of cases.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…In three previous studies the prevalence of ILAs ranged from 3% to 10%, with estimates of progression ranging from 20% at 2 years to 46% at 4 years [6,12,13]. In a recently published study by ARAKI et al [14], the results were comparable: ILAs were prevalent in 6% of total cases, and in 3% (n=53) of the initial scans, of which 43% (n=23) demonstrated progressive imaging abnormalities over ∼6 years of follow-up time. Consistent with previous reports, the progression of ILAs to imaging findings consistent with usual interstitial pneumonia (UIP) was seen in 4% of cases.…”
mentioning
confidence: 81%
“…Consistent with previous reports, the progression of ILAs to imaging findings consistent with usual interstitial pneumonia (UIP) was seen in 4% of cases. ILAs have been defined in the majority of those studies as bi-basal reticular changes (around 80% of ILA cases showed this pattern in the study by ARAKI et al [14]), with a large minority that progressed and, for those who progress, a significant increase in the risk of death (HR 3.9, 95% CI 1. [15].…”
mentioning
confidence: 99%
“…In general, progression of HRCT abnormalities is associated with increased mortality. In an analysis of nearly 2000 patients in the Framingham heart study [43], 6% were found to have worsening interstitial lung abnormalities on serial computed tomographies, which was associated with increased mortality (hazard ratio of 3.9). Serial HRCTs may be able to identify a subset of patients with more rapid progression of disease.…”
Section: Prognosismentioning
confidence: 99%
“…In four recent cohorts, the presence of ILAs was associated with a significant increase in mortality (15), and in the study of Araki and colleagues, ILA progression was predictive of a fourfold increase in the risk of death (3). It is these findings that indicate that the goal of achieving earlier IPF diagnosis is plausible and should be pursued, but it is essential that the correct ILA subgroup be selected for further study.…”
mentioning
confidence: 99%
“…Given that ILAs can, in fact, be characterized morphologically, exactly as is routine practice in established interstitial lung disease, it is increasingly important that abnormalities compatible with early IPF (i.e., subpleural reticular ILA) be evaluated more selectively than has been the case in many reports. The separation between fibrotic and nonfibrotic ILAs, made in a number of studies (3,(8)(9)(10)(11)(12)(13)(14), is not sufficient in itself, as limited fibrosis is variably present in smoking-related respiratory bronchiolitis and in many other non-IPF contexts. Even in studies in which ILA subgroups have been clearly described, important clinical associations have mostly been defined for ILAs as a single amalgamated entity.…”
mentioning
confidence: 99%